1999
DOI: 10.1097/00001756-199903170-00003
|View full text |Cite
|
Sign up to set email alerts
|

Medial prefrontal cortex generates frontal midline theta rhythm

Abstract: Frontal midline theta rhythm (Fm theta) is a distinct theta activity of EEG in the frontal midline area that appears during concentrated performance of mental tasks in normal subjects and reflects focused attentional processing. To tomographically visualize the source current density distributions of Fm theta, we recorded Fm theta by using a 64-channel whole-head MEG system from four healthy subjects, and applied a new analysis method, synthetic aperture magnetometry (SAM), an adaptive beam forming method. Fm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

28
269
1
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 437 publications
(299 citation statements)
references
References 6 publications
28
269
1
1
Order By: Relevance
“…However, for a dipole that is placed either at the nearest suprathreshold voxel, or at the local maximum in the medial frontal cluster that explains the most variance, the dipole fit was qualitatively similar to the unconstrained fit. Interestingly, Ishii et al (1999) used a beamformer approach on MEG data to estimate the location of the theta source, and located it in a region that largely overlaps with the medial frontal fMRI cluster observed in this experiment. If the cluster is the source location of the frontal theta activity, the substantial size of this cluster suggests a distributed source for frontal theta.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…However, for a dipole that is placed either at the nearest suprathreshold voxel, or at the local maximum in the medial frontal cluster that explains the most variance, the dipole fit was qualitatively similar to the unconstrained fit. Interestingly, Ishii et al (1999) used a beamformer approach on MEG data to estimate the location of the theta source, and located it in a region that largely overlaps with the medial frontal fMRI cluster observed in this experiment. If the cluster is the source location of the frontal theta activity, the substantial size of this cluster suggests a distributed source for frontal theta.…”
Section: Discussionmentioning
confidence: 95%
“…The first line of evidence is that it has been shown that the medial frontal cortex (our major cluster) is a likely source of frontal theta activity. Source modeling attempts have located the source of frontal theta effects in medial frontal areas Gevins et al, 1997;Ishii et al, 1999;Onton et al, 2005). However, most of these attempts used equivalent dipole models and located the frontal theta in or near the anterior cingulate region, somewhat posterior and deeper than the observed medial frontal theta-BOLD cluster Gevins et al, 1997;Onton et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations